Urinary steroid profile in females – the impact of menstrual cycle and emergency contraceptives. Issue 7 (28th November 2016) - Mullen, Jenny E.; Thörngren, John‐Olof; Schulze, Jenny J.; Ericsson, Magnus; Gårevik, Nina; Lehtihet, Mikael; Ekström, Lena
Abstract : Today's doping tests involving longitudinal monitoring of steroid profiles are difficult in women. Women have more complex hormonal fluctuations than men and commonly take drugs such as hormonal contraceptives that are shown to affect biomarkers used in these doping tests. In this study, we followed six women's urinary steroid profile during one menstrual cycle, including both glucuronides and sulfate conjugated fractions. Additionally, we studied what happens to the steroidal module of the Athlete Biological Passport (ABP) after administration of an emergency contraceptive (levonorgestrel, NorLevo®). The study shows that there are large individual variations in all metabolites included in the ABP and that the administration of emergency contraceptives may lead to suspicious steroid profile findings in the ABP. Urinary epitestosterone concentration increased during the menstrual cycle, leading to a decrease in the testosterone/epitestosterone ratio. The ratios followed in the ABP varied widely throughout the menstrual cycle, the coefficient of variation (CV) ranging from 4 to 99%. There was a 3‐fold decrease in epitestosterone 24 h post administration of the emergency contraceptive pill and androsterone, etiocholanolone, and 5β‐ androstan‐3α, 17β‐diol concentrations decreased about 2‐fold. When analyzed with the ABP software, one of the six women had an atypical profile after taking the emergency contraceptive. Furthermore, we could not find any alterations in excretion routes (i.e., if the metabolites are excreted as glucuronide or sulfate conjugates) during the menstrual cycle or after administration of emergency contraceptive, indicating no direct effect on phase II enzymes. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Women show large individual variations in the steroids measured in the Athlete Biological Passport. The T/E ratio, traditionally very important in doping testing decreases significantly during the menstrual cycle. When analyzed in the ABP, one of the six women showed an atypical finding after administration of an emergency contraceptive. No alteration in excretion of glucuronide or sulfate fractions were found during the menstrual cycle or after administration of an emergency contraceptive